Violence Against Old People in the Countryside : On the Example of Research in Rural Communities of Podlaskie Voivodeship - Rudnik, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The old age is generally comprehended as a time of rest and life’s wisdom. Unfortunately researches and reports more often show that old people’s life not always is full of calm and appreciation. The problem that not small percentage of elderly person wrestle is elder abuse, which seems to be one of the most important social issue on the world. Interest in the phenomenon of violence against the elderly, however, emerged only in the late 70s and early 80s of the twentieth century, when it was first diagnosed it as a health and social problem. This situation was the result of the increasing role of social policy and the growing interest in domestic violence. This article is a presentation of elder abuse occurrence in Podlaskie voivodeship. Furthermore, collected empirical material let show in this case study forms of elder abuse and perpetrators. Researches which were made in three selected rural communities of Podlaskie voivodeship showed that old people more often got abuse, neglect, and aggressive behavior in the form of arguments, insults and taking their money without their consent. Perpetrators of elder abuse mainly were immediate persons as spouses and adult children. Interesting is also fact that perpetrators also were unfamiliar persons - generally neighbours and young people.